Monocentric study of 112 consecutive patients with childhood onset GH deficiency around and after transition - Courtillot, Carine; Baudoin, Roselyne; Du Souich, Tatiana; Saatdjian, Lucile; Tejedor, Isabelle; Pinto, Graziella; Léger, Juliane; Polak, Michel; Golmard, Jean-Louis; Touraine, Philippe (European journal of endocrinology, 2013)
ObjectivesOur aim was to analyze a large cohort of childhood onset GH deficiency (CO-GHD) adults from a unique adult center, in order to analyze their clinical management and to study the metabolic and bone status in relation to GHD and to the other pituitary deficits, and to evaluate these parameters during the long-term follow-up.Design and methodsObservational retrospective cohort study on 112 consecutive CO-GHD adults transferred to our unit from 1st January 1994 to 1st March 2012. Evaluation of GHD in pediatrics and after transition was conducted following consensus guidelines. Data recorded from pediatric and adult files were GH doses, pituitary magnetic resonance imaging and function, and metabolic and bone status.ResultsMost patients presented with severe CO-GHD (64%) associated with other pituitary deficits (66%). CO-GHD was acquired in 56%, congenital in 33%, and idiopathic in 11% cases. Most patients (83%) stopped GH before transfer, at 16.3 years (median), despite persistence of GHD. Median age at transfer was 19.4 years. After transfer, GHD persisted in 101 patients and four of the 11 resolutive GHD were non idiopathic. IGF1 level was <−2 SDS in 70% of treated patients at transfer and in 34% of them after 3 years of treatment. Follow-up showed improvement in lipid profile and bone mineral density in severely persistent GHD patients under GH therapy. In multivariate analysis, the associated pituitary deficits seemed stronger determinant factors of metabolic and bone status than GHD.ConclusionsThis study raises concern about discontinuation of GH replacement therapy in pediatrics in severely persistent GHD patients and about the often insufficient dose of GH in the treatment of adult patients.